1998
DOI: 10.1109/82.700924
|View full text |Cite
|
Sign up to set email alerts
|

Designing 1-V op amps using standard digital CMOS technology

Abstract: This paper addresses the difficulty of designing 1-V capable analog circuits in standard digital complementary metal-oxide-semiconductor (CMOS) technology. Design techniques for facilitating 1-V operation are discussed and 1-V analog building block circuits are presented. Most of these circuits use the bulk-driving technique to circumvent the metaloxide-semiconductor field-effect transistor turn-on (threshold) voltage requirement. Finally, techniques are combined within a 1-V CMOS operational amplifier with ra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
184
0

Year Published

2005
2005
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 362 publications
(190 citation statements)
references
References 12 publications
0
184
0
Order By: Relevance
“…Body-driven amplifiers where the body-source voltage is amplified instead of the gate-source voltage, has been already introduced for low-voltage applications [2]. But since the effective transconductance of a body-driven transistor, i.e.…”
Section: Proposed Techniquementioning
confidence: 99%
See 1 more Smart Citation
“…Body-driven amplifiers where the body-source voltage is amplified instead of the gate-source voltage, has been already introduced for low-voltage applications [2]. But since the effective transconductance of a body-driven transistor, i.e.…”
Section: Proposed Techniquementioning
confidence: 99%
“…Two-or multi-stage configurations have been used to increase the voltage gain and swing of the opamps; but due to more low-frequency poles, frequency compensation is required which limit the speed of the circuit, nevertheless, they consume more power. Therefore, novel circuit techniques applicable to single-stage architectures are required to present high-gain low-power amplifiers with little limitation on the circuit speed [1,2].…”
Section: Introductionmentioning
confidence: 99%
“…Contrary to the other types of previous differential amplifiers with a rail-to-rail common mode input range [5,6,7,8,9], the proposed amplifier has the unique Fig. 3(a) shows the AC gain of the differential amplifier and the overall open loop gain of the analog fine tuning block which is equal to A Â g m1 R. As shown in the figure, the open loop gain is 6 dB at minimum when V CONT ¼ V DD and above 20 dB when V CONT is between 0.18 V and 0.96 V. Thus, by using the proposed differential amplifier, the analog fine tuning block can have very wide V CONT range as shown in Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, a large number of research articles can be found to meet these goals specially when talking about medical equipments. The common trend for analyzing low power circuits is the lowering of supply voltage [1]. But the threshold voltage of metal-oxide-semiconductor (MOS) transistor acts as a main obstacle in lowering of voltage supply after certain limit.…”
Section: Introductionmentioning
confidence: 99%